2022
DOI: 10.1007/s12032-022-01701-3
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic natural compounds Enzastaurin and Palbociclib inhibit MASTL kinase activity preventing breast cancer cell proliferation

Abstract: Microtubule-associated serine/threonine kinase-like (MASTL) regulates mitotic progression and is an attractive target for the development of new anticancer drugs. In this study, novel inhibitory molecules were screened against MASTL kinase, a protein involved in cell proliferation in breast cancer. Natural source-derived drugs Enzastaurin and Palbociclib were selected to identify their role as MASTL kinase inhibitors. Cytotoxic activity, kinase activity, and other cell-based assays of Enzastaurin and Palbocicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In addition, in the present results, early and repeated experiences of painful stimulation caused a signi cant upregulation of MASTL in adolescent hippocampal tissue and were involved in regulating chromosome condensation and cell division processes (19)(20)(21). MASTL is active in cell cycle progression and induces the mitotic transition by inhibiting the activity of the tumor suppressor PP2A-B55 phosphatase (22).…”
Section: Discussionsupporting
confidence: 62%
“…In addition, in the present results, early and repeated experiences of painful stimulation caused a signi cant upregulation of MASTL in adolescent hippocampal tissue and were involved in regulating chromosome condensation and cell division processes (19)(20)(21). MASTL is active in cell cycle progression and induces the mitotic transition by inhibiting the activity of the tumor suppressor PP2A-B55 phosphatase (22).…”
Section: Discussionsupporting
confidence: 62%
“…The anticancer activities of the three FDA approved agents (palbociclib, ribociclib and abemaciclib) were also added for comparison and were obtained from the literature. [38][39][40][41] All data and results (IC 50 ) are summarized in Table 5. The results shown in Table 5 revealed that all compounds had promising cytotoxic activity against both MCF-7 and MDA-MB-231 cell lines with inhibitory activity ranging from 0.891 to 36.4 μM and 1.91 to 81.46 μM, respectively.…”
Section: 22mentioning
confidence: 99%
“…The combined of CDK4/6 inhibitor Palbociclib and MEK inhibitor PD0325901 elicited a robust therapeutic response in KRAS-dependent and BRAF mutant colorectal cancer, both in vitro and in vivo. 50 Polisety et al 51 found that Enzastaurin and Palbociclib possessed the ability to induce cell death in breast cancer cells and exhibited significant synergistic therapeutic potential. Borre et al 52 found that combined PLX4720 and Dasatinib treatment induced apoptosis, increased immune cell infiltration, and reduced tumor volume in anaplastic thyroid cancer.…”
Section: Performance Comparison In the Inductive Experiments (Cold St...mentioning
confidence: 99%